The Role of the Pohuwato Regency Government in Carrying Out Disaster Mitigation in Marisa District - Mohammad Fajar Abdjul (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research aimed to find out and describe the role of Regional Government of Pohuwato District in mitigating disaster in Marisa Sub-district, and to find out as well as to describe factors which inhibit the role of Regional Government of Pohuwato District in mitigating disaster in Marisa Sub-district. The research finding showed that the role of Regional Government of Pohuwato District in mitigating disaster in Marisa Sub district has been conducted in accordance with vision and mission. Subsequently, it was shown by the role of Head of Regional Disaster Management Agency who executed every management properly and better as well as quickly and decently in accordance with the demand of the situation. In addition, the factors which inhibited the role of Regional Government of Pohuwato District in mitigating disaster in Marisa Sub-district were a human condition, nature, and also the behavior of citizen eho had lack of understanding on the danger of disaster risk which led citizen to refuse the appeal and invitation of the Regional Disaster Management Agency.